Comparative Analysis Of Industry Development Of Islamic Banking System In Malaysia And Nigeria - Muhibat Ayoni Oladimeji; Muhammad Ridhwan Ab. Aziz; Khairil Faizal Khairi (DISC International, 2024)
Purpose: The purpose of the study is to critically evaluate the industry development of Nigerian Islamic banking system in terms of its establishment and operation using Malaysian experience as the base. The study also provides useful suggested recommendations as a way forward for the development and for the smooth running of the system. Methodology: Qualitative research method was employed by the study which consists of documentary review and face to face in-depth interview. with regulatory officers, practitioners, academicians who are directly involved in the operations of Islamic banking system in two countries Malaysia and Nigeria. And secondary source inform of documentary review is also employed. Findings: From the findings of this study, in terms of basic minimum things, most, but not all of the situations regarding shariah governance, in Nigeria are in line with footsteps of Malaysia. Thus, lots need to be done. The regulators should bear it in mind that in terms of shariah governance framework what they are have done are just the basic minimum required for the start, they should be prepared and ready for the comprehensive effective and efficient frameworks for the industry. Practical Implication/ Value of the Study: the study will have policy implication to the CBN and other stakeholders in the area of Islamic banking system. Findings of this study will be a source of reference for Nigeria and other countries in formulating the similar concept of Islamic banking system. The findings of the study will also help the management of the Islamic bank operators in the industry on how they should direct their management policies towards strategic tools to use in order to be able to reap industry’s potentials. The study will also add to the pool of available literature available on the subject matter.